Analisis Numerik Perilaku Rangka Beton Bertulang dengan Dinding Pengisi - Budiwati, Ida Ayu Made; Dharma Giri, Ida Bagus (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
The behavior of reinforced concrete frame with infill wall (RDP) has been studied numerically by modeling the RDP structure using the LUSAS software. The results were compared to other researchers’ results that conducted laboratory test and used SAP programs. The results of analysis using SAP show that the proposed model that subjected to load up to the maximum limit show similar behavior to the laboratory tests results in which parameters such as secant modulus for concrete and wall materials based on graphs of stress-strain relationships and a reduction in moment of inertia due to the crack of beam-column are taken into account. The model using LUSAS did not adopt this method instead applied plastic elastic material and non-linear analysis. The results of the analysis are still not in proportional to the magnitude of the laboratory test results, but the behavior of the load and deflection indicates similar form. The analysis models show the maximum stress points that occur on the wall similar to that with the pattern of failure in laboratory testing. The maximum stress occurs at the opening corner and the beam column joint corner that is in line with the results of laboratory testing.